Adolescents who were born very preterm have decreased brain volumes - Nosarti, Chiara; Al‐Asady, Mazin H. S.; Frangou, Sophia; Stewart, Ann L.; Rifkin, Larry; Murray, Robin M. (Brain (London, England : 1878), 2002)
Infants born very preterm have an increased risk of brain injury. Given the great increase in the number of such infants that are surviving, it is important to establish whether any resultant brain abnormalities persist into adolescence and adult life. We therefore examined in vivo whole brain, grey matter, white matter and hippocampal volumes, ventricular size and grey/white matter ratios in a series of adolescents who had been born very preterm, and an age‐matched full‐term control group. Structural MRI was carried out on a cohort of 72 adolescents (mean age 15 years) who were born before 33 weeks, and 48 age‐matched full‐term controls. Brain measurements were made blind to group affiliation using stereological principles. After controlling for gender and height, the very preterm subjects showed a 6.0% decrease in whole brain volume, and an 11.8% decrease in cortical grey matter volume, as well as a 15.6% decrease in right and a 12.1% decrease in left hippocampal volumes; they also had a 42.0% increase in the size of the lateral ventricles. Therefore, individuals who were born very preterm continue to show noticeable decrements in brain volumes and striking increases in lateral ventricular volume into adolescence. The functional significance of these abnormalities merits further investigation.